PENGALIHAN KREDITUR MELALUI CEASIE （STUDI KASUS PADA KOPERASI SIMPAN PINJAM INDOSURYA ） - Sri Eni Julianita Koto (Jurnal Perspektif Hukum, 2021)
The state of liquidation of each bank and non-bank financial institution is strongly affected by social and economic conditions, both on a national and international scale. In order for lending (loans) to continue to run, it is known that the accounts receivable transfer agency is known as cessie. Based on Article 613 of the Civil Code, it is stated that the delivery of receivables in the name and other bodily objects is carried out by making an authentic deed or deed under the hands of which the rights to property are delegated to others. The delivery of these receivables has no effect on the debtor before delivery is notified and approved in writing or acknowledged by the Debtor / Borrower. The existence of an authentic deed or underhand deed is needed as a way of transferring or transferring ownership rights over the receivables in question from the creditor to a third party. The role and authority of a Notary in the making of cessie documents, as regulated in the notary office law, namely "Notary is a public official who has the authority to make authentic deeds and has other powers as referred to in the notary office law. Receivables transferred by cessie are a claims held by creditors against their debtors which are claims on behalf of. In principle, a bill in the name shows clearly and definitely about the creditor who is entitled to receive payment. This occurred in the transfer of accounts receivable between the Indosurya Savings and Loans Cooperative (Old Creditors) and Indosurya Inti Finance (As the new creditors). The transfer of accounts receivable that occurs between the Indosurya Savings and Loans Cooperative and Indosurya Inti Finance has a legal effect on the collateral binding that has been installed by the mortgage and has legal consequences for the borrower / debtor of the Indosurya savings and loan cooperative who switches from the Cooperative Borrower who is subject to the regulations of the Ministry of Cooperatives and Small Business and Medium to become Indosurya Inti finance debtors who are subject to the regulations of the Financial Services Authority.The problems in this research, among others: How is the transfer of accounts receivable by cessie and the consequences for guarantees of mortgage rights, How is the implementation of collection of accounts receivable (cessie) made with a notary deed, How is the implementation of cessie in indosurya savings and loan cooperatives. The problems in this study include: How is the transfer of accounts receivable by cessie and the consequences for guarantees of mortgage rights, How is the implementation of collection of accounts receivable (cessie) made with a notary deed, How is the implementation of cessie in indosurya savings and loan cooperatives. This research uses legal certainty theory and legal protection theory. This research uses normative legal research methods that are descriptive in nature, the data sources of this study can be divided into primary data and secondary data. Primary data was conducted in order to obtain field research through interviews with informants. Library research is carried out by reading books, journals, and laws and regulations. The results showed that. The transfer of accounts receivable (Cessie) between the old creditor and the new creditor which is guaranteed by the mortgage right causes the mortgage to also be transferred. The law states that if the receivables secured by mortgage rights are transferred due to cessie, subrogation of mortgage rights is also transferred due to the law. The role of a notary in the production of a cessie deed is the same as that of other deeds made by a notary. As a deed made before / made by a Notary Public has Construction, namely the Authority, requirements and procedures that must be carried out by the Notary Public. . The implementation of Accounts Receivable Transfer (Cessie) between the Indosurya Savings and Loan Cooperative and Indosurya Inti Finance has legal consequences for both the borrower and the new creditor (cessionaris). The implementation of the cessie has not been carried out as it should be regulated in the provisions of the law. Accounts receivable transfer is only carried out in an operational system, debtor loans are transferred to the operational system of Indosurya Inti Finance. Accont management (loans) is still maintained by the Indosurya Savings and Loans Cooperative. this causes losses incurred on the borrower (Debtor) and results in legal uncertainty. Article 16 of the mortgage rights law confirms that receivables are transferred due to cessie, and the mortgage rights are transferred due to law to new creditors. In the implementation of the cessie between Indosurya savings and loan cooperatives and the core indosurya finance, the mortgage rights have not been registered again. The deviation from the practice of implementing this cessie is not mentioned in the law, namely Article 16 of Law No. 4 of 1996. In juridical terms, the absence of the transfer of the security right causes the cessei agreement to be null and void or it is assumed that the transfer of accounts receivable has not yet occurred. In a sociological view, the non-registration of mortgage rights does not make the cessie cancel. The agreement has no material rights, because material rights have the principle of publicity. Publicity principle is a security right that must be registered. So that creditors change from preferred creditors to become concurrent creditors